FGF gene family characterization provides insights into its adaptive evolution in Carnivora. Issue 14 (29th June 2021) - Wei, Qinguo; Dong, Yuehuan; Sun, Guolei; Wang, Xibao; Wu, Xiaoyang; Gao, Xiaodong; Sha, Weilai; Yang, Guang; Zhang, Honghai
Abstract: Fibroblast growth factors (FGFs) encoded by the FGF gene family can regulate development and physiology in animals. However, their evolutionary characteristics in Carnivora are largely unknown. In this study, we identified 660 sequences of three types of FGF genes from 30 unannotated genomes of Carnivora animals (before 7th May 2020), and the FGF genes from 52 Carnivora species were analyzed through the method of comparative genomics. Phylogenetic and selective pressure analyses were carried out based on the FGF genes of these 52 Carnivora species. The phylogenetic analysis results demonstrated that the FGF gene family was divided into 10 subfamilies and that FGF5 formed one clade rather than belonging to the subfamilies of FGF4 and FGF6 . The evolutionary analysis results showed that the FGF genes were prominently subjected to purifying selection and were highly conserved in the process of Carnivora evolution. We also carried out phylogenetic comparative analyses, which indicated that the habitat was one of the factors that shaped the evolution of Carnivora FGF genes. The FGF1 and FGF6 genes were positively selected in the Carnivora animals, and positive selection signals were detected for the FGF19 gene in semiaquatic Carnivora animals. In summary, we clarified the phylogenetic and evolutionary characteristics of Carnivora FGF genes and provided valuable data for future studies on evolutionary characterization of Carnivora animals. Abstract : We identified 660 new sequences of three types of FGFs genes from 30 Carnivora animals' unannotated genomes, and 1, 144 FGFs genes from 52 Carnivora species were analyzed through the method of comparative genomics. The phylogenetic analysis clarified the classification of Carnivora FGF gene family. We found that FGFs genes mainly undergone purifying selection and the positively selected signals were found in FGF1, FGF6, and FGF19, which might be associated with the adaption of these animals for their diet habit and predation style. We also found that the habitat is one of the factors that shaped the evolution of Carnivora FGFs genes.